Molecular Characteristics of Carbapenem-Resistant Enterobacter cloacae in Ningxia Province, China - Shi, Zhiyun; Zhao, Huizheng; Li, Gang; Jia, Wei (Frontiers in Microbiology, 2017)
The emergence of carbapenem-resistant Enterobacteriaceae (CRE) has become a major public health concern worldwide and a new challenge in the treatment of infectious diseases. The molecular characteristics of Enterobacter cloacae in Ningxia China are unknown. In this study, we reported 10 carbapenem-resistant E. cloacae isolates from the General Hospital of Ningxia Medical University, the largest university hospital in Ningxia between January 2012 and December 2013. Bacteria isolates were identified by Vitek2 compact and the identity of non-duplicate E. cloacae isolates was further confirmed by PCR and sequencing. The drug susceptibility and phenotype identification of these isolates were analyzed by agar dilution method, modified Hodge test (MHT) and EDTA synergy test. Beta-lactamase (bla) genes blaNDM-1 was found in 8 out of 10 isolates. Most isolates harboured multiple resistance genes including blaESBL, blaAmpC, quinolones, aminoglycosides and disinfectant resistance genes. Pulsed field gel electrophoresis (PFGE) showed that these E. cloacae isolates were grouped into 6 clusters based on a cutoff of 80% genetic similarity. In conjugative assay, 9 out of 10 isolates transferred carbapenem-resistant genes to Escherichia coli. Our study has revealed that NDM-1-producing isolates are the most prevalent carbapenem-resistant E. cloacae in Ningxia. These isolates also carry several other carbapenem-resistant genes and can transfer these genes to other bacteria through conjugation. These findings highlight an urgent need to monitor these isolates to prevent their further spread in this region.